Chronic Alcoholic Liver Disease and Mortality Risk in Spontaneous Bacterial Peritonitis: Analysis of 6,530 Hospitalizations - Bhandari, Renu (Cureus, 2020)
Objective Our study aimed to assess the risk of in-hospital mortality due to chronic alcoholic liver disease (CALD) and other comorbidities in spontaneous bacterial peritonitis (SBP) inpatients. Methods We conducted a cross-sectional study using the Nationwide Inpatient Sample (NIS, 2012 to 2014) from the United States and included 6,530 patients (age 18-50 years) with a primary diagnosis of SBP. Logistic regression was used to evaluate the odds ratio (OR) for in-hospital mortality in SBP by comorbidities. Results The prevalence of CALD in SBP patients is 43.6%, and a higher proportion were males (68.8%) and whites (67%). Middle-aged adults (OR 2.8, 95% CI 1.74-4.45) had higher odds of in-hospital mortality in SBP patients. Race and sex were non-significant predictors for mortality risk. Patients with comorbid coagulopathy (OR 1.9, 95% CI 1.45-2.48) and heart failure (OR 3.9, 95% CI 2.46-6.36) have increased mortality in SBP inpatients. After controlling confounders, CALD was significantly associated with increased in-hospital mortality (OR 1.5, 95% CI 1.12-1.94) in SBP inpatients. Conclusion CALD is an independent factor in increasing the risk of in-hospital mortality in SBP patients by 48%. Alcohol use screening, and alcohol abstinence and supportive therapy need to be implemented at an earlier stage to improve health-related quality of life and reduce in-hospital mortality in SBP patients.